61. Arthrocnemo macrostachyi-Sarcocornietum hispanicae, a new halophytic plant community from eastern Iberian Penisula - de la Fuente, Vicenta; Rufo, Lourdes; Teijeiro, Ana; Sánchez-Mata, Daniel (Lazaroa, 2013)
Abstract: Fuente, V. de la, Rufo, L. & Sánchez-Mata, D. Arthrocnemo macrostachyi-Sarcocornietum hispanicae, a new halophytic plant community from eastern IberianPenisula. Lazaroa 34: (2013).A new phytosociological association, Arthrocnemo macrostachyi-Sarcocornietum hispanicae, to frame the halophytic vegetation structured bySarcocornia hispanica throughout saline habitats in eastern Iberian Peninsula isproposed. Some phytosociological remarks on Salicornietea fruticosae syntaxonomicaltypology are also given.